Pharmacokinetics and metabolite profiling of fimasartan, a novel antihypertensive agent, in rats. (October 2014) - Kim, Tae Hwan; Shin, Soyoung; Bashir, Mohammad; Chi, Yong Ha; Paik, Soo Heui; Lee, Joo Han; Choi, Hyuk Joon; Choi, Jin Ho; Yoo, Sun Dong; Bulitta, Jürgen B.; Ma, Eunsook; Joo, Sang Hoon; et al.
Abstract 1. <?ri?>The objectives of this study were to evaluate the pharmacokinetics and metabolism of fimasartan in rats. 2. <?ri?>Unlabeled fimasartan or radiolabeled [14C]fimasartan was dosed by intravenous injection or oral administration to rats. Concentrations of unlabeled fimasartan in the biological samples were determined by a validated LC/MS/MS assay. Total radioactivity was quantified by liquid scintillation counting and the radioactivity associated with the metabolites was analyzed by using the radiochemical detector. Metabolite identification was conducted by product ion scanning using LC/MS/MS. 3. <?ri?>After oral administration of [14C]fimasartan, total radioactivity was found primarily in feces. In bile duct cannulated rats, 58.8 ± 14.4% of the radioactive dose was excreted via bile after oral dosing. Major metabolites of fimasartan including the active metabolite, desulfo-fimasartan, were identified, yet none represented more than 7.2% of the exposure of the parent drug. Fimasartan was rapidly and extensively absorbed and had an oral bioavailability of 32.7–49.6% in rats. Fimasartan plasma concentrations showed a multi-exponential decline after oral administration. Double peaks and extended terminal half-life were observed, which was likely caused by enterohepatic recirculation. 4. <?ri?>These results provide better understanding on the pharmacokinetics of fimasartan and may aid further development of fimasartan analogs.